Rotating instability on steam turbine blades at part-load conditions - Zhang, L (2013)
A computational study aimed at improving the understanding of rotating instability in the LP steam turbine last stage working under low flow rate conditions is described in this thesis. A numerical simulation framework has been developed to investigate into the instability flow field. Two LP model turbine stages are studied under various flow rate conditions. By using the 2D simulations as reference and comparing the results to those of the 3D simulations, the basic physical mechanism of rotating instability is analysed. The pressure ratio characteristics across the rotor row tip are found to be crucial to the inception of rotating instability. The captured instability demonstrates a 2D mechanism based on the circumferential variation of unsteady separation flow in the rotor row. The 3D tip clearance flow is found not a necessary cause of the instability onset. Several influential parameters on the instability flow are also investigated by a set of detailed studies on different turbine configurations. The results show that the instability flow pattern and characteristics can be altered by the gap distance between the stator and rotor row, the rotor blading and the stator row stagger angle. Some flow control approaches are proposed based on the observations, which may also serve as design reference. The tip region 3D vortex flow upstream to the rotor row is also captured by the simulations under low flow rate conditions. Its appearance is found to be able to suppress the inception of rotating instability by disrupting the interaction between the rotor separation flow and the incoming flow. Finally, some recommendations for further work are proposed.